2015
DOI: 10.1074/mcp.m113.036764
|View full text |Cite
|
Sign up to set email alerts
|

Antiandrogens Act as Selective Androgen Receptor Modulators at the Proteome Level in Prostate Cancer Cells*

Abstract: Current therapies for prostate cancer include antiandrogens, inhibitory ligands of the androgen receptor, which repress androgen-stimulated growth. These include the selective androgen receptor modulators cyproterone acetate and hydroxyflutamide and the complete antagonist bicalutamide. Their activity is partly dictated by the presence of androgen receptor mutations, which are commonly detected in patients who relapse while receiving antiandrogens, i.e. in castrate-resistant prostate cancer. To characterize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…AR protein levels are influenced by antiandrogen treatment [ 50 ]. In accordance with a previous study, the unaltered AR mRNA levels suggest that antiandrogens do not affect AR expression, but rather AR protein turnover, as AR stability [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…AR protein levels are influenced by antiandrogen treatment [ 50 ]. In accordance with a previous study, the unaltered AR mRNA levels suggest that antiandrogens do not affect AR expression, but rather AR protein turnover, as AR stability [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of prostate cancer, active AR promotes tumour growth and so treatment options for prostate cancer often target this signalling axis, through the use of androgen deprivation and hormonal therapies such as antiandrogens 27 , 28 . Antiandrogens (e.g., bicalutamide (BIC) and enzalutamide (ENZA)) interact with the AR in the ligand binding pocket and hold the receptor in an inactive conformation, unable to form an active transcriptional complex, and thus inhibit its activity 29 . Importantly, previous studies have demonstrated that the AR is expressed in the lung 30 and studies using mice have confirmed that AR is functional in this organ 31 , 32 .…”
Section: Introductionmentioning
confidence: 99%
“…The combined treatment of flutamide with DHT reversed the inhibition of inflammatory biomarker secretion by RAW264.7 cells. This is probably because flutamide is a selective antagonist of the AR [38]. A similar inhibition response in macrophage RAW264.7 cells culture might be induced by environmental androgenic pollutants.…”
Section: Discussionmentioning
confidence: 99%